Smart Home Automation Using IoT Sensors and Microcontrollers - Rizki, Cindy Atika; Khairuniza, Nabila; Habibah, Muthiah (International Journal of Applied Science and Technology Application, 2026)
The rapid development of Internet of Things (IoT) technology has significantly influenced the way residential environments are managed and controlled. Smart home automation has emerged as an effective solution for improving comfort, security, and energy efficiency through the integration of sensors, microcontrollers, and network communication systems. This study presents the design and implementation of a smart home automation system using IoT sensors and microcontrollers to monitor environmental conditions and automatically control household devices. The proposed system utilizes several sensors to detect parameters such as temperature, humidity, light intensity, and motion, which are processed by a microcontroller to determine appropriate system responses. Based on predefined conditions, the system can automatically activate or deactivate devices including lighting systems, ventilation fans, and security alerts. Wireless communication enables remote monitoring and control through internet-connected devices, allowing users to manage their home environment from different locations. The results show that the system operates reliably and responds quickly to environmental changes, demonstrating effective automation performance. In addition, the implementation of sensor-based control contributes to improved energy efficiency by ensuring that electrical devices operate only when necessary. Overall, the proposed IoT-based smart home automation system provides a practical and scalable approach for developing intelligent residential environments supported by modern digital technologies.